Lectura de un paisaje estratificado: propuesta de restauración basada en el ordenamiento multi-escala de las cañadas en la mesa de Xéridas, Santander, Colombia. (2017)
Along the vertical gradients from the Xeridas plateau to the canyons of the lower Chicamocha and the upper Sogamoso rivers, three landscapes are identified: high plateau, hanging valleys and canyon, corresponding to socio-ecosystemic scenarios. Physical environment, vegetation and degree of alteration of the systems that conform these landscapes are described. The history of disturbance from prehispanic to present times and the resulting patterns of ecological change point to a sequence of different means of transformation that overlap historically in this system, and that can be interpreted as a stratified landscape with a trend of degradation that continues today. The restoration model is constructed at three scales, macro, mid and micro: landscape, micro-drainages, and individual properties. The objective is to introduce at each scale a regenerative trajectory aiming to restore a dynamic equilibrium between the components of conservation, regeneration, production and shelter articulated along vertical corridors of the canyons and oriented by fair water use and conservation by highlands and lowlands.